Growth performance, rumen fermentation and meat quality of boer goats fed diets containing different parts of king of bitters (Andrographis paniculata (burm.f.) wall. ex nees) - Yusuf, Aisha Laraba (2014)
Synthetic feed additives such as antibiotics and antioxidants play a significant role in improving the health, overall performance of animals, and quality of animal products. Despite the numerous benefits derived from the use of these synthetic feed aaditives, there are also health concerns on their usage. Thus, there is a need to find alternatives to these additives in order to bridge the gap between improved animal performance and safety of animal products. Hence, the search for natural growth promoters that can stabilize digestibility, improve growth performance, quality and increase yield of product that will lead to higher profitability in any livestock venture. Therefore, the objective of this research was to evaluate the influence of feeding diets supplemented with different parts of Andrographis paniculata (AP) on growth performance, rumen fermentation and meat quality of goats. The first experiment was conducted to evaluate the amount of polyphenols in the leaf, root and stem of AP and the effects of those parts on apparent nutrient digestibility and ruminal biohydrogenation in vitro. Significantly higher concentrations of total polyphenols, non-tannin and tannin polyphenols were recorded in the leaf of AP (APL). Subsequently, three diets which contained separately, the leaves (APL), roots (APR) and stems (APS) of Andrographis paniculata at 1% (w/w) levels of inclusion were formulated, in addition to the control diet (AP0). The samples of these diets were incubated for 24 h in buffered ruminal liquor obtained from goats.The results showed that in comparison with AP0, the APL, APR and APS diets showed lower (P<0.05) concentrations of ammonium nitrogen. Thereafter, six diets containing the leaves, roots and stems of Andrographis paniculata at 1 and 2% (w/w) levels of inclusion and their effects on in vitro ruminal biohydrogenation evaluated. The control diet (AP0) was not supplemented. The assessment on rumen biohydrogenation revealed significantly a higher proportion of cis-9, trans-11 conjugated linoleic acid (CLA) and C18:3n-3 in the APR2 diet. Higher ratios of unsaturated fatty acid to saturated fatty acids (P<0.05) were also recorded in the APL2 diet. The rates of biohydrogenation of oleic, linoleic and linolenic acids were significantly higher in the APR2 diet compared to the other dietary treatments.Experiments that followed consisted of a 100-days feeding trial involving 24, four month old Boer bucks was conducted to determine the growth performance and digestibility of the diets. The animals were randomly allotted to three different dietary groups: (1) AP0 -basal diet only or control; (2) APL -basal diet + 1.5% (w/w) leaf powder of Andrographis paniculata and (3) APWP - basal diet + 1.5% (w/w) whole plant of Andrographis paniculata. In a concurrent separate experiment using fistulated goats, the effects of these diets on rumen metabolism were assessed. The dietary supplementation of different parts of Andrographis paniculata improved feed intake, feed efficiency, weight gain and body weight. Except for crude fibre and ether extract, digestibility of the other nutrients were significantly higher (P<0.05) in the APL and APWP than the AP0 diet. Both APL and APWP diets reduced (P<0.05) the concentration of ammonium nitrogen and increased (P<0.05) total VFA and rumen pH values. The analysis of rumen free fatty acid profiles demonstrated a higher composition of CLA in the APL diet. Higher compositions of total unsaturated fatty acids, monoenoic fatty acids, total n-3 and n-6 PUFA and ratios of unsaturated fatty acids (USFA) to saturated fatty acids (SFA) and polyunsaturated to saturated fatty acids (PUFA) were noted in the APWP diet. The ratio of n-6 to n-3 was significantly (P<0.05) lower in both APL and APWP diets when compared with the AP0 diet. The real-time PCR analysis revealed a higher population density of the cellulolytic bacteria in the APWP diet. At the end of the feeding trial the goats were slaughtered and carcass characteristics and meat quality assessment were conducted. The animals were humanely slaughtered, eviscerated and longitudinally split into right and left halves the left half was assigned lean, bone and fat tissue composition determination and the right half carcasses were subjected to 0, 1 and 7 d postmortem storage at 4 °C. On each day of postmortem, the longissimus thoracis muscle (LT) samples were collected and analysed. uscle samples for fatty acid profile and proximate composition were only taken at 0 d postmortem. The results showed that in comparison with those of the AP0 group, lean to bone ratio, lean to fat ratio and percentage of lean were significantly higher (P<0.05) in samples of the APWP and APL groups. Goats fed AP0 (control) had significantly higher proportions of fat and bone than those subjected to the APL and APWP diets. At 1 and 7 d postmortem, lower pH values were indicated by the muscle samples of APL and APWP groups while a lower drip loss was recorded in samples of APWP group. However, higher cooking loss was observed in both APL and APWP samples compared with the AP0. The lightness (L*) and tenderness of LT muscle were significantly higher in APWP compared with the AP0 group. Higher concentration of CLA was indicated by the muscles of APWP group. The total USFA and the ratio of USFA to SFA in the LT muscle were significantly higher in APL and APWP, while a higher total USFA and ratio of USFA to SFA were noted in the APWP group. Lipid oxidative stability was significantly higher in APL and APWP compared to the AP0 groups. The microbiological assay of the LT muscle stored frozen for 3 and 6 months revealed higher colony forming unit (cfu) of lactic acid bacteria in APL and APWP, with higher cfu of pathogenic bacteria and total bacteria counts recorded in samples of the AP0 group. The e-nose analysis revealed higher flavour and aroma compounds in the APWP samples. Sensory evaluation, demonstrated higher preference by the taste pannelists for meat samples from animals supplemented with APWP. In conclusion, the dietary supplementation of AP improved meat quality, without any adverse effects on rumen metabolism and growth performance in goats. However, the diet containing the whole plant (APWP) was found to be more effective than those containing only the leaf (APL), although all parts of the plant were found to contain polyphenols.